Drama, Philosophy, Politics in Ancient Greece. Contexts and Receptions (BIBLIOTECA UNIVERSITÀRIA, 2014)
This book is focused mainly, though not exclusively, on ancient Greek drama. It aims at examining the integration of various kinds of texts in the society and the whole body of discourses of their time, as well as in the previous and later tradition. Each chapter analyses one particular case of such integrations and is a sample of the new ways to explore the relationship between texts and literary genres. On the whole the book shows why we need to find more complex ways to describe the relationship between texts and genres in ancient Greece, and to refine the distinction between the various periods of ancient Greek culture.